Reducing early-stage Cleantech funding gaps: an exploration of the role of Environmental Performance Indicators. Issue 9 (16th August 2022) - Harrer, Theresia; Owen, Robyn
Abstract : Purpose: The purpose of this paper is to explore why, despite the development of a hybrid investing logic, funding problems are so persistent for early-stage Cleantech ventures ("Cleantechs"). An institutional logics lens is adopted to analyze how key actors' perceptions and communications of the Cleantech value proposition shape information asymmetries (IAs). Design/methodology/approach: A mixed methods approach draws on 82 Cleantech pitch decks and 31 investment guidance documents, and insights from interviews with 42 key informants and nine Cleantech CEOs and their investors. Findings: IAs persist, first of all, because key investor and entrepreneurial actors combine different goals in the hybrid Cleantech value proposition. Interestingly, the analysis of Environmental Performance Indicators (EPIs) as a critical communication tool reveals a further mismatch in how actors actually combine logics. The authors ultimately identify three emergent actor roles – traditional laggard, developer and boundary spanner – that present a framework of how the three most influential actor groups develop EPIs and via that a hybrid Cleantech financing logic to overcome IAs. Originality/value: The paper enhances the entrepreneurial finance literature primarily by showing that in contexts of hybrid investing a more nuanced understanding of institutional logics in terms of ends and means is critical to overcome IAs. While prior works highlight goal incompatibilities, the findings here suggest that the (in-)compatibility of goals as well as EPI choices of the same actors is likely to be the key explanandum for the stickiness of IAs and the funding gap. The novel emerging role framework offers additional theoretical, policy and practical advances for hybrid logic development.